Regional Geology of the Hypanis Valles System, Mars. Issue 3 (13th March 2022) - Adler, Jacob B.; Bell, James F.; Warner, Nicholas H.; Dobrea, Eldar Noe; Harrison, Tanya N.
Abstract: We present a geomorphic map of the Hypanis Valles watershed and a geomorphic map of the Hypanis deposit region at its terminus. We mapped these two regions at different scales: 1:2, 000, 000 for the catchment map (−5° to 10°N and 300°–315°E) and 1:500, 000 for the Hypanis deposit map (10°–13.0°N and 313°–316.5°E). Our mapping provides new morphologic insights beyond previous efforts which used lower spatial resolution data. We defined units based on morphology, albedo, thermal inertia, elevation, and spectral parameters. We propose that episodic volcanism and aqueous activity filled the Chryse basin from the early Noachian. Hypanis Valles was active during the Noachian, forming the Hypanis terminal deposits in the southern Chryse region. Hundreds of kilometer‐sized mounds and cones stratigraphically post‐date Hypanis fluvial deposition as these features appear to have erupted or effused through all other major map units. We propose sedimentary diapirism or mud volcanism may be responsible for these features, a hypothesis consistent with the compressional wrinkle ridge tectonism in a sedimentary basin. Future work could further investigate the formation of these cones and mounds and better assess their astrobiologic importance. Plain Language Summary: We present a new geologic map of the largest proposed river delta deposit on Mars and the upstream region that contributed sediments. We investigate the source materials that Hypanis Valles eroded to better estimate the composition of units in the downstream deposits. We used high‐resolution orbital images and data sets to map the region previously proposed as an ancient ocean shoreline environment. The terrain is more diverse than previous maps suggest. We identified cone and mound features which may indicate recent eruption of buried sediments and could provide additional targets for future study and exploration alongside the proposed delta. Key Points: We mapped the Hypanis Valles watershed and deposit region Fan sediments were likely sourced from mid to late Noachian units with diverse lithologies Cones and mounds suggest remobilization of buried sediments